2021
DOI: 10.1186/s12876-021-01834-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the operative outcomes and learning curves between laparoscopic and “Micro Hand S” robot-assisted total mesorectal excision for rectal cancer: a retrospective study

Abstract: Background The Micro Hand S robot is a new surgical tool that has been applied to total mesorectal excision (TME) surgery for rectal cancer in our center. In this study, we compared the operative outcomes, functional outcomes and learning curves of the Micro Hand S robot-assisted TME (RTME) with laparoscopic TME (LTME). Methods A total of 40 patients who underwent RTME and 65 who underwent LTME performed by a single surgeon between July 2015 and No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(19 citation statements)
references
References 28 publications
(30 reference statements)
0
19
0
Order By: Relevance
“…Studies were published between 2009 and 2021, with a total of six prospective studies [ 11 , 23 27 ], 34 retrospective studies [ 9 , 10 , 12 , 14 , 15 , 28 56 ], and five studies in which the design was not clearly described [ 8 , 13 , 57 59 ]. Thirteen studies reported on the learning curve of L-TME [ 10 12 , 26 , 27 , 39 44 , 58 , 59 ], twenty on the learning curve of R-TME [ 13 – 15 , 23 25 , 28 35 , 52 57 ], eight on the learning curve of TaTME [ 8 , 9 , 36 – 38 , 48 50 ], and four reported on the comparison of the learning curve of two approaches [ 45 47 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Studies were published between 2009 and 2021, with a total of six prospective studies [ 11 , 23 27 ], 34 retrospective studies [ 9 , 10 , 12 , 14 , 15 , 28 56 ], and five studies in which the design was not clearly described [ 8 , 13 , 57 59 ]. Thirteen studies reported on the learning curve of L-TME [ 10 12 , 26 , 27 , 39 44 , 58 , 59 ], twenty on the learning curve of R-TME [ 13 – 15 , 23 25 , 28 35 , 52 57 ], eight on the learning curve of TaTME [ 8 , 9 , 36 – 38 , 48 50 ], and four reported on the comparison of the learning curve of two approaches [ 45 47 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Thirteen studies reported on the learning curve of L-TME [ 10 12 , 26 , 27 , 39 44 , 58 , 59 ], twenty on the learning curve of R-TME [ 13 – 15 , 23 25 , 28 35 , 52 57 ], eight on the learning curve of TaTME [ 8 , 9 , 36 – 38 , 48 50 ], and four reported on the comparison of the learning curve of two approaches [ 45 47 , 51 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations